Políticas habitacionais em cidades amazônicas: Belém e São Luis na perspectiva comparativa - PORTELA, Roselene de Souza (Universidade Federal do Pará, 2019)
This work analyzes the management models of housing policies implemented in the Amazon s cities, particularly in Belém (PA) and São Luís (MA), as well as the impacts on the city spatial organization and the relation with the existent social and spatial segregation. Emphasis is given to the challenges faced by urban management in the two cities and how the State deals with social problems. We intend to go beyond spatial exclusion forms and use a social and spatial approach in order to evaluate the potential transformation that might be linked to daily practices in the city, which ought to be acknowledged as legitimate actions by public policies. In order to achieve our goal, we use a theoretical construction to gather information on housing policy in Brazil and in the Amazon region. It is therefore necessary to analyze the urban space construction and housing, based on the capitalist logic, which had a great concentrating and excluding influence in the urban development of the two Amazon cities, resulting in a social and spatial segregation process. The study was carried out through a comparative method, allowing us to identify the differences and similarities between two management experiences in the housing policies applied in two municipalities of the Amazon region, Belém and São Luís. The study focuses on housing policy planning and management processes, targeting social contradictions and intervention strategies. Therefore, the methodological procedures used in this work are: bibliographic and documental research, statistical data collection; interviews with experts and management staff from governmental institutions related to housing programs or projects; and direct observation. The results lead us to conclude that, regardless the management model used (technocratic or participative), the housing policy has not shown structural advances. Therefore, the actions implemented by programs/projects did not contribute to reduce the social and spatial segregation pattern and did not change the housing concept in those two cities.